Heterogeneous productivity in voluntary public good provision: An experimental analysis - Gerlinde Fellner; Yoshio Iida; Sabine Kröger; Erika Seki (Institute for the Study of Labor (IZA), 2011)
This article experimentally examines voluntary contributions when group members' marginal returns to the public good vary. The experiment implements two marginal return types, low and high, and uses the information that members have about the heterogeneity to identify the applied contribution norm. If agents are aware of the heterogeneity, contributions increase in general. However, high types contribute more than low types when contributions can be linked to the type of the donor but contribute less otherwise. Low types, on the other hand, contribute more than high types when group members are aware of the heterogeneity but contributions cannot be linked to types. Our results underline the importance of the information structure when persons with different abilities contribute to a joint project, as in the context of teamwork or charitable giving.
urn:nbn:de:101:1-201104133783
Keywords: C9; H41; 330; public goods; voluntary contribution mechanism; heterogeneity; information; norms; Öffentliches Gut; Arbeitsgruppe; Wohltätigkeit; Verteilungskonflikt; Informationsverhalten; Soziale Norm; Verhaltensökonomik; Test